The EU e-commerce market in a pandemic context – linking demographic factors and territorial convergence - Stângaciu, Ancuța; Țimiraș, Laura; Zaiț, Luminița; Nichifor, Bogdan; Danu, Marcela; Harja, Eugenia (Journal of Business Economics and Management, 2024)
This article presents a comprehensive analysis of the European Union’s e-commerce market within the context of the COVID-19 pandemic. It examines the correlation between demographic factors and the territorial convergence of e-commerce activities across EU member states. By leveraging empirical data and employing the General Linear Model – Repeated Measures (GLM-RM) to analyze temporal changes in the phenomena of interest across EU countries, the study provides a nuanced understanding of the market’s evolution during and after the pandemic. The research reveals a notable expansion in the EU’s e-commerce market value, leading to a reduction in economic disparities among member states. It highlights the role of consumer demographics in shaping online shopping behavior, with age being a pivotal factor that demonstrates significant variations. Additionally, the study delves into the differential performance of various product categories, reflecting a pattern of selective sectoral convergence. A key finding is the pandemic’s dual role as a disruptor and an accelerator for digital integration, particularly in enhancing digital inclusivity in less economically developed EU regions. This study contributes to the broader discourse on e-commerce market dynamics in times of global crises, offering valuable insights for policymakers and business strategists.